Penatalaksanaan Fisioterapi pada Pasien Ostheoarthritis Genue Bilateral Di RSUD DR.Moewardi Surakarta - Untari, Novia Widi, Wahyuni S.ST FT M.Kes (2016)
Background : Ostheoarthritis (OA) is an inflammation of the bone is marked by pain, limitation of motion, joint stiffness and weakness in the quadriceps muscle. Ostheoarthritis (OA) can occur at the age of 45 years and older. In such cases can be dealt with physiotherapy modalities. Physiotherapy in these cases can improve facial muscle strength and improve functional activities face with infrared modalities, eletrical stimulation and exercise therapy. Objective : To determine the physiotherapy management in case Genue Bilateral Ostheoarthritis in reducing pain, improving muscle strength, increase LGS knee joints and improve functional activities face with Infrared modalities, Electrical Stimulation, exercise therapy. Results : After 6 times therapy pain relief obtained their results from the motion T1: 5.2 into T6: 4.9, increased muscle strength than the value of T1: 4 to T6: 5, LGS increase of active movements T1: S = 00-00 -1500 became T6: S = 00-00-1200, passive movements T1: S = 00-00-1200 becomes T6: S = 00-00-1250. Conclusion : Delivery of infrared, electrical stimulation and exercise therapy can reduce pain, improve muscle strength, increase LGS knee joints, and improve functional activity in patients Ostheoarthritis face Bilateral Genue.